If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(m + 12) = 5m Reorder the terms: 7(12 + m) = 5m (12 * 7 + m * 7) = 5m (84 + 7m) = 5m Solving 84 + 7m = 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. 84 + 7m + -5m = 5m + -5m Combine like terms: 7m + -5m = 2m 84 + 2m = 5m + -5m Combine like terms: 5m + -5m = 0 84 + 2m = 0 Add '-84' to each side of the equation. 84 + -84 + 2m = 0 + -84 Combine like terms: 84 + -84 = 0 0 + 2m = 0 + -84 2m = 0 + -84 Combine like terms: 0 + -84 = -84 2m = -84 Divide each side by '2'. m = -42 Simplifying m = -42
| 10p=s | | 5x+17+2x=17++4x | | 2b+5+3=10 | | y=x+20 | | (4x^2)-5=3x | | 0.2(5x-20)+7=5(3x+1) | | 3(y+1)=2(y-3) | | -0.6666x-1=0.3333x+3 | | -2x+x=0 | | 10-3y=5y-22 | | 2x+5(x-6)=12 | | x+5-11=2 | | 73x(5x-19)=180 | | 2p^2-3-2=0 | | (3x+2)(x-3)=0 | | 4(3-2x)+3=4x+5 | | 9x-4(x+3)=18 | | 4(2x-5)-x=7(x+6) | | 6x+3-4x=x-7 | | 5x+10=25y | | 2(x+1)-3(x-2)=x-6 | | 14-10x=179-45x | | 772-6x=7x+20 | | 66-2x=7x+16 | | 7.05a-2=4.25a+26.25 | | 4x+8x=46+x | | 440h-275=55 | | 10x+8=87+x | | 55h-275=440 | | 5a=2a+6 | | 21x^2-50x-613=0 | | 21x^2-50x^2-613=0 |